A Bibliometric Overview of Current States and Research Trends in Concrete-Filled Tube Columns - Jen Hua Ling; Armstrong Ighodalo Omoregie (Journal of Civil Engineering, 2025)
Concrete-filled tube (CFT) columns have gained prominence in structuralengineering for their exceptional load-bearing capacity and efficiency. This studyconducts a bibliometric analysis of 1,154 publications from 2014 to August 2024,using data from the Scopus database and VOSviewer, to map research trends andkey developments in CFT studies. Citation, co-citation, and co-authorshipanalyses identify influential publications, journals, authors, countries, andinstitutions. Findings highlight significant growth in research output andincreasing focus on advanced modelling techniques, including machine learning.Emerging themes include integrating alternative materials such as FiberReinforced Polymer (FRP), stainless steel, High-Performance Concrete (HPC),Recycled Aggregate Concrete (RAC), and Seawater Sea Sand Concrete(SWSSC), showcasing the potential of multi-material innovations. This analysisoffers insights into current research directions and identifies gaps, suggesting thatfuture work explore novel material combinations and advanced modellingapproaches to enhance performance and drive innovation in CFT column studies.